Nutrient Adsorption onto Sawdust for the Treatment of Stormwater - Harmayani, Kadek Diana (Curtin University, 2013)
In this study, the sawdust of radiata pine wood was chosen as an adsorption medium to remove nutrients from stormwater. A series of batch and column experiments was carried out and a mass transfer correlation was developed to investigate the capability of sawdust in removing dissolved nutrients. The results indicate that sawdust is a promising adsorbent medium for nutrient removal. The findings of this research may be useful in designing biofiltration/bioretention systems for treating stormwater.